Progress in Stem Cell Transplantation - Demirer, Taner (IntechOpen, 2015)
This book documents the increased amount of stem cell-related research, basic and clinical applications as well as views for the future. The book covers a wide range of issues related to new developments and innovations in cell-based therapies discussed in basic and clinical chapters from authors around the world involved in stem cell studies and research. It thereby complements and extends the basic coverage of stem cells, such as mesenchymal stem cells, effect of stem cells on aging, cover hematopoietic stem cells, storage and cryopreservation, issues related to clinical applications such as haploidentical transplants and use of stem cells for the treatment of Huntingtons disease. Clearly, the treatment of various malignant and nonmalignant diseases depends heavily on stem cells, and this book is well positioned to provide comprehensive coverage of these developments.